2019
DOI: 10.1002/path.5317
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal transition and increased therapy resistance of glioblastoma cells is related to astrocyte reactivity

Abstract: Grade IV astrocytoma/glioblastoma multiforme (GBM) is essentially incurable, partly due to its heterogenous nature, demonstrated even within the glioma‐initiating cell (GIC) population. Increased therapy resistance of GICs is coupled to transition into a mesenchymal (MES) cell state. The GBM MES molecular signature displays a pronounced inflammatory character and its expression vary within and between tumors. Herein, we investigate how MES transition of GBM cells relates to inflammatory responses of normal ast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 52 publications
0
31
0
Order By: Relevance
“…MES is the most malignant glioblastoma and has a worse prognosis [ 24 ]. On the one hand, it has stronger resistance to treatment than other types of gliomas [ 25 ]. This therapeutic resistance may be related to the high expression of inflammation-related genes and NF-kB activation [ 8 ], which is consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MES is the most malignant glioblastoma and has a worse prognosis [ 24 ]. On the one hand, it has stronger resistance to treatment than other types of gliomas [ 25 ]. This therapeutic resistance may be related to the high expression of inflammation-related genes and NF-kB activation [ 8 ], which is consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation-related genes are also highly expressed in the MES subtype [ 8 , 33 35 ]. Epithelial-to-mesenchymal transition is a common pattern of increased malignant behavior and disease progression of epithelial tumors, and the MES phenotype is closely related to this change [ 25 ]. This finding supports our GSEA results.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that ectopic expression of CD133 in glioma cells could promote neutrophil recruitment by regulating IL-1β and its downstream chemokines 14 . In addition, IL-1β could significantly promote the self-renewal of glioma stem cells, and trigger the transition of glioma-initiating cells into a mesenchymal (MES) cell state 44,45 . In this study, we found that the expression of IL-1β steadily decreased after knockdown of LINC01116, thereby reducing neutrophil recruitment and glioma proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Glioblastoma is one of the most lethal types of tumors in the central nervous system [12]. Surgery section, chemotherapy and radiotherapy were widely adopted to treat patients with malignant brain tumor whereas the result of these methods did not improve patient’s condition [13]. The pathology and progression of glioblastoma was associated with both genetic and epigenetic changes [14].…”
Section: Discussionmentioning
confidence: 99%